Effect Of Aerobic Exercise Training On Pulmonary Function Tests: A Pragmatic Randomized Controlled Trial - CHAITRA B.; PANDURANG NARAHARE; NAGARAJA PURANIK; VIJAY MAITRI (International Journal of Pharma and Bio Sciences, 2011)
The aim of the study was to evaluate the effect of aerobic exercise training on pulmonary function tests in young healthy volunteers. We recruited eighty, apparently healthy medical students of either sex, aged 17-20 years. Randomization into experimental and control groups (40 each), was carried out with a table of random numbers. Experimental group participated in a 16 weeks aerobic exercise plan, while control group had no plan of exercise during that period of time. Pulmonary Function Test was recorded before the commencement of training and at the end of 16 weeks in both the groups. The data were analyzed by paired’ test. P < 0.05 was considered significant. After 16 weeks of aerobic training there was significant improvement in pulmonary functions in the experimental group (P < 0.05). In conclusion, the current study has shown that, there is significant positive relationship between aerobic training and pulmonary function tests.